Political Responsibility for a Globalised World After Levinas' Humanism - Wolff, Ernst (Der Mensch im Netz der Kulturen - Humanismus in der Epoche der Globalisierung / Being Human: Caught in the Web of Cultures - Humanism in the Age of Globalization, 2011)
The aim of this book is to reflect on the complex practice of responsibility within the context of a globalised world and contemporary means of action. Levinas' exploration of the ethical serves as point of entry and is shown to be seeking inter-cultural political relevance through engagement with the issues of postcoloniality and humanism. Yet, Levinas fails to realise the ethical implications of the inevitable instrumental mediation between ethical meaning and political practice. With recourse to Weber, Apel and Ricoeur, Ernst Wolff proposes a theory of strategic co-responsibility for the uncertain global context of practice.